2016
DOI: 10.4314/sajas.v46i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inclusion of discarded cabbage (<i>Brassica oleracea</i> var. <i>capitata</i>) on the growth performance of South African Dorper lambs

Abstract: A study was conducted to determine the effect of dietary inclusion of discarded cabbage (DC) on the intake and growth performance of lambs. Diets containing 0 (control, DC0), 100 g DC/kg (DC100), 150 g DC/kg (DC150) and 200 g DC/kg (DC200) were fed ad libitum to 36 South African Dorper lambs (22.0 ± 1.3 kg live weight). The dry matter intake (DMI) and lamb growth performance was reduced as the level of cabbage in the diet increased. The feed conversion rate of lambs was negatively affected by inclusion of cabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It was noted that NDF digestibility provides an accurate estimation of intake ( Harper and McNeill, 2015 ). A correlation between NDF digestibility and intake was stated by Nkosi et al (2016) who noted a lower DMI for lambs fed fresh Brassica ( oleracea var. capitata ) compared to a Brassica-free diet (1,420 vs. 1,600 g).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It was noted that NDF digestibility provides an accurate estimation of intake ( Harper and McNeill, 2015 ). A correlation between NDF digestibility and intake was stated by Nkosi et al (2016) who noted a lower DMI for lambs fed fresh Brassica ( oleracea var. capitata ) compared to a Brassica-free diet (1,420 vs. 1,600 g).…”
Section: Discussionmentioning
confidence: 86%
“…It has been stated that increased concentrations of fresh cabbage ( Brassica oleracea var. capitata ) in the diet of lambs reduced OM and NDF digestibility (73% vs. 65%; 56% vs. 47%, respectively; Nkosi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…e rumen microbes of ruminants can convert the fibres into useful nutrients. Studies have shown that inclusions of some of the residues/wastes (apple, banana, cabbage, chicory, citrus, grape, mango, peas, pineapple, and pumpkin) in poultry and livestock rations have significantly improved the animals' general well-being and reproductive traits [16][17][18][19][20][21][22][23].…”
Section: Selected Agricultural Residues In Livestock Nutritive Diet Omentioning
confidence: 99%
“…Cabbage leaves are a good source of nutrients in ruminants and are known for significantly improving the growth parameters of the ruminants. e antioxidant activities of cabbage included in livestock rations aid in protecting the livestock against a variety of diseases, ensuring well sustained growth, reproduction, and development for ruminants [22]. Despite the growing popularity of cabbage as a nutritive livestock feed in temperate agricultural regions, high water content (8.6% dry matter) and antinutritive components discourage their use [53].…”
Section: Nutritious Dietary Resources Derived From B Oleraceamentioning
confidence: 99%